Review of Fly Ash-Based Zero-Cement Concrete Performance - Fuqaha, Sameh; Zaki , Ahmad; Nugroho, Guntur (UIR Press, 2025)
The urgent need to reduce the environmental impact of construction materials has led to increasing interest in sustainable alternatives to Ordinary Portland Cement (OPC). Among emerging solutions, Zero-Cement Concrete (ZCC) utilizing fly ash (FA) as a primary binder offers a viable pathway for lowering CO₂ emissions and reusing industrial by-products. This review investigates the key components, mixing mechanisms, curing conditions, and mechanical performance of FA-based ZCC. FA, particularly Class F and Class C, in combination with alkaline activators such as sodium hydroxide (NaOH) and sodium silicate (Na₂SiO₃), plays a crucial role in the geopolymerization process that forms the cementitious matrix. The compressive strength, modulus of elasticity, and flexural strength of ZCC are influenced by multiple factors, including activator molarity, SS/SH ratio, binder-aggregate proportions, and curing regime. Experimental studies indicate that with optimized mixing and curing parameters, FA–ZCC can achieve mechanical performance comparable to or exceeding OPC concrete. However, the absence of standardized mix design procedures and field-curing strategies remains a challenge. This study highlights the need for further research on durability, life-cycle assessment, and in-situ applications to fully realize the potential of ZCC as a mainstream, eco-efficient construction material.